Aspectos morfofuncionais renais de vítimas de queimaduras admitidas em um centro especializado - Souza, João Paulo Fernandes (2022)
Acute Kidney Injury (AKI) is characterized by abrupt interruption of renal function, with decreased urinary flow and increased metabolic residues. It has clinical conditions with wide etiologies, which makes the definition and diagnosis even more challenging. Burns are trauma to organic tissues, which can be caused by electrical energy, thermal energy, and radiation. At the site of the lesion, hyperemia, stasis and necrosis (autophagy, apoptosis and cell death) can be characterized, in addition to the systemic inflammatory response, which aims to reduce local damage. That said, it is the objective of this study to verify the occurrence of renal dysfunction in burn victims who were admitted to a Burn Treatment Center (CTQ). This is a prospective, cross-sectional study according to the guidelines (Strengthening the Reporting of Observational Sdudies in Epidemiology (STROBE). A study was conducted in a tertiary hospital, in the city of Fortaleza, between October and December 2020 and January 2021. A sample was obtained from the medical records of hospitalized patients, from the formula for finite population. Data collection was performed by a structured instrument. 137 medical records were analyzed, and after the inclusion and exclusion criteria resulted in a final sample of 92 medical records. The project was approved by the ethics committee of the hospital that hosted the study, with a favorable opinion (Opinion number: 3,892,924). Graphpad Prism software ® v.8.0.1 was used for statistical analysis. In the present study, there was a higher prevalence of male sex (71.74%), of the 92 patients who were burned, 66.30% were second-degree and 33.70% third-degree burns, the main etiologic agent was fire (25%), and mean burned body surface (SCQ) was 19.89%. Acute Kidney Injury (AKI) was observed in 59.78% of the patients, in the three stages of kidney diseases: Improving Global Outcomes (KDIGO), with increased creatinine and urea in the first 48 hours, of these patients 11.96% evolved with need for Renal Replacement Therapy (RRT) and 8.70% died. It is concluded that patients with second and third-degree burns have a higher risk of AKI. Other intra-hospital factors may also be associated with worsening kidney function, such as surgeries, hospitalization in an intensive care unit, use of vasoactive drugs, infections, use of antibiotics, and the need for mechanical ventilation.